2020
DOI: 10.1186/s12890-020-1162-6
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre retrospective observational study on Polish experience of pirfenidone therapy in patients with idiopathic pulmonary fibrosis: the PolExPIR study

Abstract: Background: Pirfenidone is an antifibrotic agent approved for the treatment of idiopathic pulmonary fibrosis (IPF). The drug is available for Polish patients with IPF since 2017. The PolExPIR study aimed to describe the real-world data (RWD) on the Polish experience of pirfenidone therapy in IPF with respect to safety and efficacy profiles. Methods: This was a multicentre, retrospective, observational study collecting clinical data of patients with IPF receiving pirfenidone from January 2017 to September 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
11
1
Order By: Relevance
“…In our series, the median increase in FVC was 2.7% of predicted, and a decrease in TLCO was 0.8% of predicted (data not shown) and none of the study participants were excluded from further analysis because of a lung function decline surpassing the threshold of 10% of baseline FVC. Of note, we found a significant decrease in BMI after six months of treatment with pirfenidone, which is consistent with earlier findings on the adverse effects of this drug [39,40]. Despite the lack of differences in EBC VEGF-A between IPF patients and controls and between IPF patients at baseline and after six months of treatment with pirfenidone, our findings provide some new data supporting the usefulness of VEGF-A as a marker in IPF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our series, the median increase in FVC was 2.7% of predicted, and a decrease in TLCO was 0.8% of predicted (data not shown) and none of the study participants were excluded from further analysis because of a lung function decline surpassing the threshold of 10% of baseline FVC. Of note, we found a significant decrease in BMI after six months of treatment with pirfenidone, which is consistent with earlier findings on the adverse effects of this drug [39,40]. Despite the lack of differences in EBC VEGF-A between IPF patients and controls and between IPF patients at baseline and after six months of treatment with pirfenidone, our findings provide some new data supporting the usefulness of VEGF-A as a marker in IPF.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Yoshikawa et al, an FVC decline of ≥10% and/or a TLCO decline of ≥15% of baseline was observed in 34.7% of the investigated group after six to nine months of observation [38]. Majewski et al reported a more favorable treatment response, with FVC and TLCO stability in 60.8% and 87.1% of the patients over six months of treatment with pirfenidone, respectively [39]. In our series, the median increase in FVC was 2.7% of predicted, and a decrease in TLCO was 0.8% of predicted (data not shown) and none of the study participants were excluded from further analysis because of a lung function decline surpassing the threshold of 10% of baseline FVC.…”
Section: Discussionmentioning
confidence: 96%
“…Second, participants were highly motivated and deemed taking medication important, confirming available evidence [ 25 ]. Only 3% of our participants reported having discontinued pirfenidone based on their own initiative, which is slightly lower than other real-world studies, reporting a 5.5–6% discontinuation rate of pirfenidone [ 26 , 27 ]. However, we detected problems with adherence already early after treatment initiation (19.6% at week six), and nonadherence increased over time (up to 36.4% at year two).…”
Section: Discussioncontrasting
confidence: 63%
“…The authors presumed that efficacy of pirfenidone in IPF patients with severe lung function impairment may diminish after 6 months of treatment [ 27 ]. In a multicenter retrospective IPF study, Majewski et al found that the median annual decline in FVC during the first year of pirfenidone therapy was −20 mL and during the second year was −120 mL ( n = 307); this decline was even less than that noted in the ASCEND trial, in which mean decline from baseline in FVC was −235 mL in the pirfenidone group over 52 weeks [ 21 , 28 ]. Similarly, in another real-world study focusing on long-term use of pirfenidone in the large cohort ( n = 502) of Japanese IPF patients, Bando et al reported a mean decline of FVC of −30 mL and of −158 mL in the first and second year of therapy, respectively [ 29 ].…”
Section: Discussionmentioning
confidence: 99%